Pengaruh Corporate Social Responsibility Terhadap Nilai Perusahaan Dengan Prosentase Kepemilikan Manajemen Sebagai Variabel Moderating (Studi Empiris Pada Perusahaan Yang Terdaftar di Bursa Efek Indonesia) - Dony Hidayat (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2019)
This research aims is to know the influence of corporate social responsibility towards the firm value and Percentage of management ownership as moderating variables. Goal of this research is to know: (1) The influence of Corporate Social Responsibility to the firm value, (2) The influence of Percentage of management ownership as moderating variables in the relationship between Corporate Social Responsibility and the firm value. The data used are secondary data. Data obtained from the Consumer Goods companies listed in the Indonesian Stock Exchange (IDX). After the sample selection is done in accordance with the criteria specified, the obtained research sample of 34 companies. The tools to analyze the data used in this research is multiple regression analysis. The conclusions of this research are: (1) Corporate Social Responsibility (X1), the percentage of management ownership (X2) and insteraction of Corporate Social Responsibility with the percentage of management ownership (X1X2) are simultaneously with evident effect on the firm value. (2) Corporate Social Responsibility (X1) not significantly partialy affect the firm value, but the percentage of management ownership included as a moderating variable, Corporate Social Responsibility and insteraction of Corporate Social Responsibility with the percentage of management ownership (X1X2) have a significant effect on the firm value, while the percentage of management ownership not significantly affect the firm value at Consumer Goods Companies in Indonesia Stock Exchange.